What is meant by social pedagogical research into foster children? - Klaus Wolf (Social Work & Society, 2017)
The way in which foster children grow up and develop is a subject dealt with by various disciplines with widely varying epistemological positions and research methods. In many countries, there are well-developed, well-established clinical research methods based on medical and psychiatric paradigms. In such cases, quantitative studies are generally carried out to examine how disorders occur and can be treated among children in care, and the results are published in corresponding international journals. The research results are also frequently used to make further enhancements in practice, thus affecting the programmes implemented in that field. Their aim is often to improve children's developmental opportunities by developing and applying effective forms of therapy. Following the medical paradigm, the focus is then on targeted treatment using programmes which have been clinically tested and evaluated in terms of their effectiveness.